Pemilihan Kualitas Gambir dengan Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) - Muhammad Iqbal; Sumijan (Jurnal Informasi dan Teknologi, 2021)
Gambier (gambir plantae) is an half of perdu plantation which in separated in several regions of Indonesia. It is especially live in Sumatra, Java, Maluku, and Burneo. In West Sumatra province, gambir is used to component for menyirih (betle) and also the farmer of gambir asproduction as. It is reserving from hot water. Extraction come from the leaves and twigs of gambir in depositor forms, then printed and then turned into dried forms. The gambir farmers usually sell their productions to the collectors with a certaibty prices. Gambir has many qualities based from it processing, catechin contains, colors, ash contains, water contains, and also its density. Some its barries often occurs from the gambir processing being into product, which a minusly quality suffers, that cause gambir price in decrease or not to expensive conditions in the market by using support decision by Multi-Objective Optimization by Ratio Analysis (MOORA) methode is a multi objektives system from which can be optimated some atributes whom contradicting each other in simultaneously, either lost profit (cost) or getting profit (benefit), the system using these methode used to choose some gambir qualified form for determine its price. These data of sample taken form Pesisir Selatan gambir, which the research result farmed that gambier ranked can be as support as some decisions to make the best gambir as price decision as. Form theseresearch could be conclude that the best gambir have an higher catechin contains, low water contains, a slightly ash contains, with a yellowish skin, and have as highest as density. Based on the data of sample of research, the best gambier in qualified in getting from Siam and pian with the grade in 0.163 with the good one criteria condition. From gambier standardization, all of gambier which have upper grade standars, qualified into good gambier quality, gambier with high quality or good can give an expensive price that encourages some gambir farmers in motivation to process gambir product being increase gambier quality that can be improve the price selling gambir as well as the purchase of gambier products.